International Higher Education Research and Comparative Analysis - Kosmützky, Anna; Krücken, Georg (International Higher Education, 2015)
The article investigates whether international comparative higher education research has grown considerably during the past two decades. It reports the outcomes of a recent bibliometric study which found three key characteristics of international comparative higher education research: a relatively steady state, a larger share of international collaborative articles in international comparative research compared to non-comparative research, and a preference for small-scale country clusters for comparison.